2021
DOI: 10.1002/lsm.23479
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of hyperspectral imaging to quantify perfusion changes during the modified Allen test

Abstract: Objectives To evaluate the capability of hyperspectral imaging (HSI), a contact‐less and noninvasive technology, to monitor perfusion changes of the hand during a modified Allen test (MAT) and cuff occlusion test. Furthermore, the study aimed at obtaining objective perfusion parameters of the hand. Methods HSI of the hand was performed on 20 healthy volunteers with a commercially available HSI system during a MAT and a cuff occlusion test. Besides gathering red‐green‐blue (RGB) images, the perfusion parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…The false color images generated with the HSI-device were transferred into MATLAB (version 2018b The MathWorks Inc., Natick, Massachusetts, USA) to derive the NIR-index, StO 2 , THI and TWI tissue indices. For each body part, a square region of interest (ROI) of 50 × 50 pixels, corresponding to 15 × 15 mm 2 on the skin surface, was selected based on a standardized method adapted from a recently published study 59 . The ROI was defined near the center of the image, and no visible blood vessels or shaded areas at the edge of the skin surface were included in the analyzed area, as this could influence the results for the calculation of the tissue indices and reduce the comparability of the results.…”
Section: Methodsmentioning
confidence: 99%
“…The false color images generated with the HSI-device were transferred into MATLAB (version 2018b The MathWorks Inc., Natick, Massachusetts, USA) to derive the NIR-index, StO 2 , THI and TWI tissue indices. For each body part, a square region of interest (ROI) of 50 × 50 pixels, corresponding to 15 × 15 mm 2 on the skin surface, was selected based on a standardized method adapted from a recently published study 59 . The ROI was defined near the center of the image, and no visible blood vessels or shaded areas at the edge of the skin surface were included in the analyzed area, as this could influence the results for the calculation of the tissue indices and reduce the comparability of the results.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] As HSI provides spectral information about hemoglobin, water and oxygen supply, it has great potential in perfusion monitoring. First studies showed its potential benefit in the microcirculation monitoring in critically ill patients on intensive care units, 4 for the assessment of the superficial palmary arch before radial artery harvest, 5 and in the identification of cutaneous perforators before harvesting an anterolateral thigh flap. 6 Perfusion monitoring is crucial in the postoperative surveillance of flaps.…”
Section: Introductionmentioning
confidence: 99%